2022
DOI: 10.1038/s41534-022-00580-w
|View full text |Cite
|
Sign up to set email alerts
|

Error measurements for a quantum annealer using the one-dimensional Ising model with twisted boundaries

Abstract: A finite length ferromagnetic chain with opposite spin polarization imposed at its two ends is one of the simplest frustrated spin models. In the clean classical limit the domain wall inserted on account of the boundary conditions resides with equal probability on any one of the bonds, and the degeneracy is precisely equal to the number of bonds. If quantum mechanics is introduced via a transverse field, the domain wall will behave as a particle in a box, and prefer to be nearer the middle of the chain rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…They are similar to the multi-qubit variable mappings used on D-Wave machines for minor embedding [62][63][64]. However, unlike the SK spin glasses, finding the ground state of spin chains can be solved efficiently classically, and they have been shown to exhibit counter-intuitive statistical effects [57], so they are not suitable for gaining insight into the behavior of more general types of problem Hamiltonians. Nonetheless, they are important for real hardware architectures (e.g.…”
Section: Definitions Of Problems Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…They are similar to the multi-qubit variable mappings used on D-Wave machines for minor embedding [62][63][64]. However, unlike the SK spin glasses, finding the ground state of spin chains can be solved efficiently classically, and they have been shown to exhibit counter-intuitive statistical effects [57], so they are not suitable for gaining insight into the behavior of more general types of problem Hamiltonians. Nonetheless, they are important for real hardware architectures (e.g.…”
Section: Definitions Of Problems Usedmentioning
confidence: 99%
“…We have numerically tested our innovations on small instances of three problems: Sherrington-Kirkpatrick (SK) spin glasses as studied in [56]; maximum independent set; and Ising spin chains with random couplings. However, spin chains have been found to exhibit counter-intuitive statistical effects [57], so will not necessarily provide a good guide for how other types of problems behave. Understanding the behavior for Ising spin chains is important in relation to minor embedding techniques used to instantiate highly connected problems into less connected hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Studies with this aim were conducted by comparing D-Wave data with (simulated) QA and classical models often including, among others, Simulated Annealing (SA). Such studies either showed that previously considered classical models cannot reproduce the D-Wave results, for instance for freeze-out time vs. temperature (Johnson et al, 2011), for success probability distributions over many random spin glass instances (Boixo et al, 2014), and for the non-uniform probability of degenerate ground states of specially crafted problem instances where the probability of one ground state is suppressed in the quantum case and enhanced for SA (Boixo et al, 2013;Albash et al, 2015) or introduced another classical model such as noisy Boltzmann distributions (Chancellor et al, 2022), classical spin dynamics (Smolin and Smith, 2013), and spin-vector Monte Carlo (SVMC, also called SSSV model-from Shin Smith Smolin Vazirani) (Shin et al, 2014), which shows agreement with the studied D-Wave data. (ii) A second aspect is the comparison between different generations of processors to judge possible improvements.…”
Section: Introductionmentioning
confidence: 99%